2011
DOI: 10.1007/s00113-010-1946-x
|View full text |Cite
|
Sign up to set email alerts
|

Das serologische Protein S100B

Abstract: Serological protein S100B measurement may be helpful as a screening test to identify patients with higher risk of traumatic brain injury for further diagnostic assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…A recent metaanalysis including .2000 patients showed a combined sensitivity of 94 % (95% CI, 88-98%) and a combined specificity of 44% (95% CI, 30-58%) with diagnostic odds ratio of 10.3 (95% CI, 4.2-24.9%). 10 Muller et al 31 concluded in a consensus paper that the biomarker can triage patients to CCT, again with a high NPV and decrease the large number of normal CCT and set free capacities of the emergency rooms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent metaanalysis including .2000 patients showed a combined sensitivity of 94 % (95% CI, 88-98%) and a combined specificity of 44% (95% CI, 30-58%) with diagnostic odds ratio of 10.3 (95% CI, 4.2-24.9%). 10 Muller et al 31 concluded in a consensus paper that the biomarker can triage patients to CCT, again with a high NPV and decrease the large number of normal CCT and set free capacities of the emergency rooms.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent meta-analysis, combined sensitivity can reach up to 94% [95% confidence interval (CI), 88-98%] and a combined specificity is only 44% (95% CI, 30-58%). [10][11][12] Some reports have also shown raised concentrations of the biomarker in patients with non-traumatic parenchymal lesions such as infections 13 and extracranial injuries. 14 As MHI is very common and imaging is associated with significant costs and radiation exposure, an additional risk parameter could be of great value to stratify the patients at risk for TBI to undergo CCT.…”
Section: Introductionmentioning
confidence: 99%